Comparing the Effectiveness of Emotional Efficacy Therapy and Integrated Transdiagnostic Treatment on Psychological Fatigue in Women Involved in Emotional Divorce with Early Marriage - AbdolHamid Rastgar; Emad Yousefi; Leila Khajepoor (Iranian Journal of Educational Research)
Objective: The objective of the current investigation was to evaluate the comparative efficacy of emotional efficacy therapy versus integrated transdiagnostic therapy on psychological fatigue among women experiencing emotional divorce as a consequence of early marriage. Methods: This research was designed as a quasi-experimental study employing a pre-test and post-test framework along with a control group, aligning with its intended aims. The sample population comprised 45 women engaged in emotional divorce, all of whom were diagnosed by licensed psychologists at counseling centers located in Shiraz. Participants were selected through convenience sampling from the pool of women seeking counseling services and were randomly allocated into three groups of 15 individuals each (with one control group consisting of 15 participants and two experimental groups totaling 30 participants). Data collection was conducted utilizing the Multidimensional Fatigue Inventory (MFI) as a measurement instrument. The analysis of the data was executed through SPSS software, encompassing covariance analysis. Results: The findings revealed that both integrated transdiagnostic therapy and emotional efficacy therapy were effective in alleviating psychological fatigue among women undergoing emotional divorce and early marriage; however, there was no statistically significant difference in the effectiveness between the two therapeutic approaches, integrated transdiagnostic therapy and emotional efficacy therapy. Conclusions: The results predominantly endorse two therapeutic approaches: integrative transdiagnostic therapy and emotional efficacy therapy, which have been identified as efficacious interventions for psychological fatigue in women who experiencing emotional divorce.